Інноваційні інструменти маркетингових досліджень в маркетинговій товарній та комунікаційній політиці торговельних закладів - Krupenna, Inga; Budnikevich, Iryna; Cherdantseva, Irуna (Економіка та право, 2020)
The article considers the directions of application of innovative tools of marketing research in the processes of formation of marketing commodity and communication policy of trade establishments. The options for companies to use artificial intelligence tools and in-depth site analysis in the marketing commodity and communication policy of FMCG market players are generalized. Prospects, advantages and problems of using Big Data Analysis as an innovation of marketing research in the field of retail are outlined. Areas of marketing innovations in FMCG are structured based on the application of big data. It is noted that the management of leading companies in the field of food retail should pay attention to the available budget information technologies Big Data and ensure their quality implementation in the system of marketing communications. The tasks that Big Data Analysis technology is able to solve in the processes of formation and implementation of marketing commodity and communication policy of local and regional retail chains, other retail business operators are identified. It has been proven that Big Data in itself does not give any compe titive advantage and only its proper use can give the marketing of the retail network an understanding of how to act properly. Some data collection tools that are most effective in offline retail, online retail are considered. The directions of search of decisions on development of actions on overcoming of consequences of corona crisis by the analytical tools which can adjust a commodity and communication policy of trade establishments are defined.
INNOVATIVE TOOLS OF MARKETING RESEARCH IN MARKETING COMMODITY AND COMMUNICATION POLICY OF TRADE ESTABLISHMENTS
Keywords: маркетингові дослідження; маркетингові інновації; маркетингова товарна політика; Big Data Analysis; маркетингова комунікаційна політика; технології штучного інтелекту; ритейл